Implementasi Sistem Pendukung Keputusan Diagnosa Penyakit Hipertensi di Ponkesdes Banyuurip Kecamatan Ujungpangkah Kabupaten Gresik - Aini, M Anwar; Abidin, Nur; Hendi, Ade; Faqihatin, Faqihatin; Shohifah, Lailatus (Civiliza Publishing, 2024)
The aim of this PKM activity is to optimize health services by utilizing IT as a supporting tool that facilitates the performance of health workers. which will be held on January 13 2024 at Ponkesdes Banyuurip, Ujungpangkah District. This information system (IS) implementation activity goes through three stages, namely preparation, implementation and evaluation. The methods used at this planning stage are observation, interviews, and Focus Group Discussion (FGD). The implementation stages are carried out by implementing IS in partner environments as well as providing outreach to health officers regarding how IS works. The evaluation stage is carried out by reflecting on the plans that have been made and the implementation that has been carried out. The results of this activity show that the IS diagnosis matches the doctor's diagnosis with an accuracy rate of above 80%. IS also speeds up performance and tidies up data on hypertension patients at Ponkesdes Banyuurip.